Associação entre tabagismo e perda dentária em adultos e idosos no Brasil: uma análise a partir dos dados da Pesquisa Nacional de Saúde 2019 - Araujo, Amanda Rodrigues (Brasil, 2022)
Tooth loss is an important marker of population oral health, whose main causes are dental caries and periodontitis. Other factors can influence its occurrence. Studies has associated tobacco use, a harmful condition to health, to a higher prevalence of tooth loss. The aim of this study was to identify the association between smoking and tooth loss in adults aged 18 or more in Brazil. Data from the 2019 National Health Survey, a partnership between the Brazilian Geography and Statistics Institute (IBGE) and the Brazilian Health Ministry (MS) were used. The outcome was self-reported tooth loss. The explanatory variables was smoking, family income, schooling, sex and age. A descriptive analysis was performed to describe the distribution of the variables evaluated and then a regression analysis was performed to rate the association between smoking and number of missing teeth. The study estimated that the standard number of missing teeth in adults aged 18 or more was 7,66 (IC95% 7,55-7,76). The self-reported of at least one missing teeth was identified in 72,0% (IC95% 71,4-72,6) of the population, 10,3% (IC95% 10,0-10,6) total edentulous, 14,2% (IC95% 13,9-14,6) with severe tooth loss and 21,3% (IC95% 20,9-21,7) non-functional dentition. Self-reporters current smokers was 11,4% (IC95% 11,0-11,8), 64,4% (IC95% 63,8-65,0) non-smokers and 24,2% (IC95% 23,7-24,7) reported not smoking or occasional smoking at the time of the interview. The adjusted linear regression coefficients for number of missing teeth, showed that smokers or former smokers, low family income and schooling, age and women exhibited higher rates of tooth loss. Conclusion: this findings showed a high prevalence of tooth loss and smoking in the brazilian population. Demonstrated the association between smoking and tooth loss, expressing the role of behavioral risk factors in oral health, in addition to having demonstrated the negative impact of unfavorable socioeconomic status and demographic factors on tooth loss.